A potential distribution map of wintering Swan Goose (Anser cygnoides) in the middle and lower Yangtze River floodplain, China - An An; Yong Zhang; Lei Cao; Qiang Jia; Xin Wang (Avian Research, 2018)
Abstract Background Reliable information on the distribution of target species and influencing environmental factors is essential for effective conservation management. However, ecologists have often derived data from costly field surveys. The Swan Goose (Anser cygnoides), a vulnerable Anatidae species, winters almost exclusively in China’s Yangtze River floodplain, but wintering numbers have been steadily decreasing. To better safeguard this unique species, modern modeling approaches can be used to quantify and predict its suitable wintering habitat. Specifically, a potential wintering distribution map of this species is critically important. Methods This study used the maximum entropy approach to model a distribution map of this species. In total, data from 97 up-to-date sites were extracted from 1263 survey sites (excluding duplicate data). After eliminating spatial autocorrelation, 11 environmental variables, including factors related to climate, land structure, vegetation, and anthropogenic activities, were used for model prediction. Results The prediction distribution map shows that the population has concentrated mainly in the boundary area of Anhui, Hubei, and Jiangxi provinces, especially along the Yangtze River. Modeling results suggest that areas within the middle and lower Yangtze River floodplain, such as those in Hunan and Hubei provinces and the eastern coastal area of Zhejiang Province, demonstrate a potential level of “medium” suitability for this species to winter. Conclusions Results from this study provide fundamental information for the restoration and management of the Swan Goose. Our “visualized” potential distribution map can assist in planning optimal conservation strategies, and consequently may help to increase the number of wintering populations in China.